Psychological Training of Nurses for Providing Palliative and Hospice Care as a Factor of their Professionalization - Marchuk , Iryna; Borysiuk , Alla; Tymofiieva , Maryna; Marchuk , Oleksandr (Insight: the psychological dimensions of society, 2023)
The purpose of the work is to generalize the level of psychological preparation of nurses for providing palliative and hospice care as a determining factor in the acquisition of professional readiness, starting from the undergraduate period of study in institutions of higher education; and also to generalize the level of psychological preparation of nurses of general practice students of medical education, nurses of medical departments of general and palliative profiles for the analysis of this component among nurses with work experience in the relevant field. Methods. Questionnaire, subjective assessment method, “Bookshelf” method. The research results were analyzed using descriptive statistics, the Kruskal–Wallis test for three or more independent samples, Spearman’s correlation, as well as Multiple Linear Regression analysis using the method of stepwise selection technique. Results. Indicators of the level of readiness of nurses of the medical palliative care service and general medical nurses are higher than those of students of higher medical education – p≤.000001 (Kruskal–Wallis test). The results of the survey: 66.0% of general medical nurses and 54.0% of palliative care nurses show a high level of professional readiness to work with incurable patients, and 70.0% of students of higher medical education have an average with a tendency to a high general level of professional readiness to work with incurable patients. It was established that, according to Spearman’s rank correlation criterion, the level of professional readiness of nurses to provide palliative care increases with age – rs= .42 at р≤ .004. Deficient motivations prevail in 61.0% of students of higher medical education, 50.0% of palliative care nurses and 76.0% of general medical nurses. At the same time, the metamotives of righteousness and holiness, spiritual self-improvement, service and wisdom are significant only for 7.0% of higher education graduates, 16% of general medical nurses and 25.0% of palliative care nurses. The motive of serving in palliative care nurses is more pronounced (р≤.020). Multiple regression analysis indicated the importance of work experience (р≤ .003), the level of education (р≤.001), decreased focus on one’s own safety and confidence as meaningful motives (р≤.030). Discussion and conclusions. An overwhelming majority of respondents at all stages of professional training express a desire to help incurable patients. With age, the importance of this care is becoming more and more realized. For the nurses of medical palliative departments, the motive of service is more important than for others. Work experience and level of education are determining factors among other researched variables for determining professional readiness to work in the field of palliative care. At the level of undergraduate education, it is extremely necessary to include topics that help to reveal special metamotives in the initial program blocks.